Do no harm: stories of life, death and surgery - Marsh, H. Henry (Weidenfeld&Nicolson, 2014)
'Enthralling' GUARDIAN. 'Incredibly absorbing ... astonishingly candid' Bill Bryson.Winner of the PEN Ackerley Prize and the South Bank Sky Arts Award for Literature.Shortlisted for the Costa Biography Award; Duff Cooper Prize; Wellcome Book Prize; Guardian First Book Award; and Slightly Foxed Best First Biography Prize. Longlisted for the Samuel Johnson Prize for Non-Fiction. What is it like to be a brain surgeon? How does it feel to hold someone's life in your hands, to cut through the stuff that creates thought, feeling and reason? How do you live with the consequences when it all goes wrong? DO NO HARM offers an unforgettable insight into the highs and lows of a life dedicated to operating on the human brain, in all its exquisite complexity. With astonishing candour and compassion, Henry Marsh reveals the exhilarating drama of surgery, the chaos and confusion of a busy modern hospital, and above all the need for hope when faced with life's most agonising decisions.